Towards realization of longer life - Khavinson, Vladimir; Popovich, Irina; Mikhailova, Olga (Acta Biomedica Atenei Parmensis, 2020)
The current demographic situation in the world is characterized by an increase in average life expectancy, low birth rate, as well as an increase in the number of older and senior people, which is why our epoch is referred to as «the age of ageing». [...]